2018
DOI: 10.1523/jneurosci.0026-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Choice for Drug or Natural Reward Engages Largely Overlapping Neuronal Ensembles in the Infralimbic Prefrontal Cortex

Abstract: Cue-reward associations form distinct memories that can drive appetitive behaviors and are involved in craving for both drugs and natural rewards. Distinct sets of neurons, so-called neuronal ensembles, in the infralimbic area (IL) of the medial prefrontal cortex (mPFC) play a key role in alcohol seeking. Whether this ensemble is specific for alcohol or controls reward seeking in general remains unclear. Here, we compared IL ensembles formed upon recall of drug (alcohol) or natural reward (saccharin) memories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…The effects should be instantaneous and transient in the case of saccharin (signaling from the gustatory system to the midbrain dopamine neurons (Simon et al, 2006)) but are delayed by minutes and could be persistent in the case of alcohol (through activation of dopamine release and other mechanisms (Weiss et al, 1993;Vengeliene et al, 2008)). Nonetheless, it was reported that drug and natural rewards produce their long-term effects by acting on the same neuronal circuits (Kelley & Berridge, 2002;Pfarr et al, 2018). Here, we found no evidence of impaired learning due to the effects of alcohol on memory performance; the behavior of mice in the saccharin and alcohol+saccharin groups was similar.…”
Section: Discussionsupporting
confidence: 43%
“…The effects should be instantaneous and transient in the case of saccharin (signaling from the gustatory system to the midbrain dopamine neurons (Simon et al, 2006)) but are delayed by minutes and could be persistent in the case of alcohol (through activation of dopamine release and other mechanisms (Weiss et al, 1993;Vengeliene et al, 2008)). Nonetheless, it was reported that drug and natural rewards produce their long-term effects by acting on the same neuronal circuits (Kelley & Berridge, 2002;Pfarr et al, 2018). Here, we found no evidence of impaired learning due to the effects of alcohol on memory performance; the behavior of mice in the saccharin and alcohol+saccharin groups was similar.…”
Section: Discussionsupporting
confidence: 43%
“…It is unclear how sleep efficiency might affect unhealthy food cravings. One potential mechanism may be that insufficient continuous sleep detrimentally affects brain development including the prefrontal cortex, which controls food cravings [34] and continues to develop throughout adolescence [35]. Poor sleep efficiency may influence the brain's ability to recover during the sleep period and impair the brain's ability to regulate.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources suggest that the IL may fulfill a more general role in forming cue–reward associations, as it has been noted that cue‐induced seeking of either alcohol or a nondrug reinforcer (saccharin) activated largely overlapping neuronal ensembles in the IL, which were of similar size and organization (Pfarr et al, ). Further complicating the notion that the Prl and IL serve generally opposing “go‐stop” functions with respect to behavior, Moorman and Aston‐Jones () found cue‐evoked activity in both the PrL and the IL during reward seeking and extinction, such that neuronal activity in both mPFC subregions appeared to be contextually driven—that is, both PrL and IL encoded behavioral initiation during reward seeking and behavioral inhibition during extinction.…”
Section: Involvement Of the Mpfc In Drug Seekingmentioning
confidence: 99%